The Role of Women's Activities in Increasing Family Income - Vira Ayu Silvidayana (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This research aims to find out the active role of women in increasingfamily income, what are the factors and their impacts. The research was conducted in several villages in Limbangan District, Kendal Regency. This research uses a qualitative descriptive method. Data collection was caried out through observation, namely by observing ongoing phenomena, interviews, namely direct dialogue with informants and complemented by data documentation. Based on the results of research that has been caried out, it shows that the role of women working in Limbangan District has a very positive and significant influence on family income. They then use the income they earn from working to increase their family income, such as: First, to increase their husband's income. Second, meet family needs. Third, some income is savedfor family needs, such as school fees, illness or other unexpected needs. It is hoped that the results of this research will be usefulfor scientific development on the theme of the active role of working women in helping to increase family income.